2024
DOI: 10.1039/d3lc00859b
|View full text |Cite
|
Sign up to set email alerts
|

AMF-SporeChip provides new insights into arbuscular mycorrhizal fungal asymbiotic hyphal growth dynamics at the cellular level

Felix Richter,
Maryline Calonne-Salmon,
Marcel G. A. van der Heijden
et al.

Abstract: Arbuscular mycorrhizal fungi (AMF) form symbiotic associations with the majority of land plants and deliver a wide range of soil-based ecosystem services. Due to their conspicuous belowground lifestyle in a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…2018). For AMF spores, Richter et al have recently presented the AMF-SporeChip , which revealed new insights into AMF spore germination and hyphal growth (Richter et al . 2024).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2018). For AMF spores, Richter et al have recently presented the AMF-SporeChip , which revealed new insights into AMF spore germination and hyphal growth (Richter et al . 2024).…”
Section: Introductionmentioning
confidence: 99%
“…The microfluidic single-cell cultivation (MSCC) device employs arrays of microchambers, allowing analysis of the germination of the filamentous bacterium Streptomyces lividans under multiple media compositions, which revealed surprising stability in behaviour despite previous observations in large-scale cultures (Koepff et al 2018). For AMF spores, Richter et al have recently presented the AMF-SporeChip, which revealed new insights into AMF spore germination and hyphal growth (Richter et al 2024).…”
Section: Introductionmentioning
confidence: 99%